Clonal selection in therapy‐related myelodysplastic syndromes and acute myeloid leukemia under azacitidine treatment. (9th March 2020) - Calleja, Anne; Yun, Seongseok; Moreilhon, Chimène; Karsenti, Jean Michel; Gastaud, Lauris; Mannone, Lionel; Komrokji, Rami; al Ali, Najla; Dadone‐montaudie, Bérangère; Robert, Guillaume; Auberger, Patrick; Raynaud, Sophie; et al.
Abstract: Introduction: Therapy‐related myelodysplastic syndrome and acute myeloid leukemia (t‐MDS/AML) are defined as complications of previous cytotoxic therapy. Azacitidine (AZA), a hypomethylating agent, has showed activity in t‐MDS/AML. Objectives: We evaluated the clonal dynamics of AZA‐treated t‐MDS/AML. Methods: We collected bone marrow samples, at diagnosis and during treatment, from AZA‐treated t‐MDS/AML patients. NGS on 19 myeloid genes was performed, and candidate mutations with a variant allele frequency >5% were selected. Results: Seven t‐AML and 12 t‐MDS were included with median age of 71 (56‐82) years old, median number of AZA cycles of 6 (1‐15), and median overall survival (OS) of 14 (3‐29) months. We observed correlation between AZA response and clonal selection. Decrease of TP53‐ mutated clone was correlated with response to AZA, confirming AZA efficacy in this subgroup. In some patients, emergence of mutations was correlated with progression or relapse without impact on OS. Clones with mutations in genes for DNA methylation regulation frequently occurred with other mutations and remained stable during AZA treatment, independent of AZA response. Conclusion: We confirmed that the molecular complexity of t‐MNs and that the follow‐up of clonal selection during AZA treatment could be useful to define treatment combination.